Podcast: Basics of Elbow Radiography - Claire Sandstrom (Association of American Medical Colleges, 2014)
Abstract This enhanced podcast explores the basics of elbow radiography, including standard views and positioning, normal elbow anatomy, and normal appearance of juxtaarticular fat pads used to assess for elbow joint effusion. This resource is targeted toward newcomers to radiology, including junior radiology residents, medical students, and non-radiology physicians. Also included are suggestions for integrating this podcast into teaching and a set of eight multiple-choice questions that can be administered only after viewing the podcast to assess comprehension. The podcast is small enough that it may be distributed as an attachment by email. The residents were sent the podcast 5 days prior to attending a noon conference on knee trauma, with instructions to download and watch it at least once but encouraged to watch as many times as desired to feel comfortable with the material. Most residents reported spending 20-30 minutes in total watching the podcast. After attending the conference, they were asked to complete an anonymous survey. Six out of six respondents reported the level of the material as "just right for where I am right now." All of the respondents reported that the podcast improved their understanding of, and ability to engage in, the subsequent conference material.